INDEXING IDENTITY THROUGH MEMES: A LINGUISTIC ETHNOGRAPHY OF MYDAYNESIA ON X - Sani, Sitti Kamila Meutia; Setyowati, Reno; Toyyib, Cholillul Rochman (Fakultas Ilmu Budaya, Universitas Mulawarman, 2026)
This study aims to examine how Indonesian K-pop fan communities, particularly Mydaynesia as the fanbase of Day6 in Indonesia, use memes as social practices to construct identity, express emotions, and position their fandom community within digital spaces. Grounded in a digital ethnography approach and framed by Silverstein’s theory of indexicality and Tusting’s concept of language as social practice, this research investigates meme practices within the Mydaynesia community on the X platform. Data were collected through one-month passive participant observation and analyzed thematically. The findings are categorized into five major themes: the use of Javanese language in fandom expression, local cultural parody, iconic Day6 song quotes, humor around military service, and delusional romance. The analysis reveals that memes are not merely a form of entertainment, but also serve as tools for building solidarity, voicing subtle critique, and shaping the community’s unique communicative style. These practices illustrate how language, humor, and local culture are combines to create shared meanings that can only be fully understood by members of the community. This study highlights the role of memes as a form of symbolic labor and communicative action that reflects values, emotions, and social bonds among members of digital Mydaynesia fandom.